External actors and the evolution of Latvian nationality policy, 1991-1999 - Morris, H; Morris, Helen M (2001)
Since regaining independence in 1991, Latvian nationality policy has developed from an exclusive, almost restitutionist, policy seeking to identity the Latvian state with the Latvian nation into a more inclusive civic definition of Latvian citizenship. This thesis aims to explain why this has occurred by examining the role of domestic, regional, and systemic level actors. Analysis of the external actors has been divided into states and institutions grouped into circles of Latvian interest. The inner circle includes Latvian domestic political actors, the next Latvia's principal bilateral relationship with the Russian Federation, followed by the Baltic States, then by Baltic Sea regional cooperation. The EU and OSCE, NATO, UN, and United States lie in the outer circles. Questions are asked about what the actors wanted in terms of Latvian nationality policy, which tools were at their disposal, and the results, if any, they were able to achieve. Although not a theoretical study, the thesis touches on theoretical and methods issues, querying the extent to which external rather than internal factors determine policy outcomes in small states and arguing that Latvia's desire to join the EU was critical in the reform of Latvian citizenship legislation. It is the author's view that the evolution in nationality policy cannot be accounted for through a single level analysis. Domestic, regional, and international bilateral contexts are all necessary aspects of an explanation, although they might not fully account for the liberalisation of the citizenship legislation. After rejection from EU accession talks and a marked deterioration in relations with the Russian Federation, the Latvian Saeima and electorate amended the Citizenship Law to conform to OSCE HCNM recommendations. This suggests that the membership conditions of the EU are a powerful force in persuading applicant countries to alter their legislation to comply with a civic concept of citizenship.